2020
DOI: 10.1021/acs.est.0c00201
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of PFOS and PFOA Toxicity on Sertoli Cells

Abstract: Perfluoroalkyl chemicals induce male reproductive toxicity. Current evidence showed the effects of the chemical exposure on the deterioration of testicular functions, and reduction in epididymal sperm counts. Previous studies showed that PFOA and PFOS displayed a high correlation with each other in seminal plasma levels, but induced different effects on semen variables. In this study, we focused on the comparative toxicity analysis of PFOA and PFOS, using a rat primary Sertoli cell model. Our transcriptomic da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…In this regard, in rodents challenged with Cd, Cur improved seminiferous tubules morphology [ 26 , 27 ] and significantly decreased the number of apoptotic germinal cells [ 28 , 29 ]. Additionally, resveratrol (Re), a polyphenol present in many plants and especially in red wine, showed antioxidant properties [ 30 ] as well a positive regulation of apoptosis and other zonula occludens protein expression, such as occludin [ 31 , 32 ]. In the testis, Re protected from oxidative stress [ 33 ], partially reversed the dysregulation of the apoptotic pathways [ 20 ], and improved sperm parameters and histopathological damage [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, in rodents challenged with Cd, Cur improved seminiferous tubules morphology [ 26 , 27 ] and significantly decreased the number of apoptotic germinal cells [ 28 , 29 ]. Additionally, resveratrol (Re), a polyphenol present in many plants and especially in red wine, showed antioxidant properties [ 30 ] as well a positive regulation of apoptosis and other zonula occludens protein expression, such as occludin [ 31 , 32 ]. In the testis, Re protected from oxidative stress [ 33 ], partially reversed the dysregulation of the apoptotic pathways [ 20 ], and improved sperm parameters and histopathological damage [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…42 It is reported that PFOS directly acts on testicular Sertoli cells in mice and disrupts BTB integrity by disturbing the expression and localization of TJ-related proteins (ZO-1, Occludin, Claudin-11) and GJ-related protein (CX43), leading to spermatogenic dysfunction and infertility. 27,43 However, there is less information on whether icariin protects testicular Sertoli cells from damage caused by PFOS. Our findings demonstrated that icariin alleviated the disruption of BTB integrity and the junctional damage of Sertoli cells by downregulating the expression levels of TJ-and GJ-related proteins in vivo and in vitro, thereby improving the PFOS-induced disorders of testicular function.…”
Section: Food and Function Papermentioning
confidence: 99%
“…Due to the widespread production and persistence, PFASs have become ubiquitous environmental contaminants . Perfluorooctanoate (PFOA) and perfluorooctanesulfonate (PFOS) are the most frequently detected PFASs in environmental compartments and are believed to exert potential toxic effects on human health. , Since 3 M Company stopped producing PFOS in 2000, the government agencies in many countries issued a series of regulations to restrict the production and application of PFOA and PFOS, , for example, PFOS was listed as an Annex B substance under the Stockholm Convention . To meet the industrial demands, many novel PFASs were widely identified and applied as their alternatives and consequently released into the environment .…”
Section: Introductionmentioning
confidence: 99%